Systematic Review and Meta-Analysis of Post-Treatment PET/CT in HPV-Associated Oropharyngeal Cancer. (June 2022) - Mathews, Fasil; Irizarry, Rachel; Rosenfeld, Richard; Sundaram, Krishnamurthi
Objective: To perform a systematic review with meta-analysis to investigate the utility of post-treatment PET/CT specifically in HPV-associated oropharyngeal squamous cell carcinoma following curative intent treatment. Methods: Random-effects meta-analysis was used to pool data from 7 observational studies (2013-2019) obtained from a database search of PubMed, Web of Science, and EMBASE using an a priori protocol with dual independent evaluation for inclusion, risk of bias assessment for acceptable methodology, and extraction of data for analysis. PET/CT results, treatment failure, imaging and interventions subsequent to PET/CT findings, and efficacy of salvage therapy were extracted. Results: Of the 907 post-treatment scans, PET/CT results were largely negative (76.2%; 95% CI, 63.4-85.6) and least often positive (11.3%; 95% CI, 8.8-14.4). PET/CT results were equivocal for 22.5% (95% CI, 12.5-36.9) and equivocal/positive for 34.2% of patients (95% CI, 25.1-44.5). Patients with an initial positive scan had the highest treatment failure rates (43.1%; 95% CI, 21.4-67.7) and those with an initial negative scan had the lowest rates (7.4%; 95% CI, 5.7-9.7). The equivocal and equivocal/positive scans had intermediate prevalence of 16.5% (95% CI, 9.4-27.6) and 16.7% (95% CI, 9.1-28.7), respectively. Conclusion: The low treatment failure rate following a negative PET/CT scan is reassuring, but the data are consistent with treatment failure rates up to 9.7% suggesting follow-up of these patients is prudent. Additionally, the low positive predictive value for treatment failure observed alludes to use of post-treatment PET/CT in HPV-associated disease frequently leading to unnecessary subsequent imaging and intervention.